Peningkatan Pengetahuan dan Kesiapsiagaan Remaja Putri Melalui Hygiene Menstruasi pada Situasi Bencana - Nurul Aziza Ath Thaariq; Mardiani Bebasari; Faridah BD; Lita Angelina Saputri; Iin Prima Fitriah; Rati Purnama Sari; Wulandari Defera; Yussie Ater Merry; Yuanita Sandra (CV. CENDIKIA JENIUS INDONESIA, 2026)
This community service program aimed to improve the knowledge and disaster preparedness of adolescent girls regarding menstrual hygiene management in disaster situations at MTSN 2 Mentawai Islands. The program was implemented through health education using presentations, group discussions, and question-and-answer sessions involving 50 female students from grades VII, VIII, and IX on May 29–30, 2026. Program evaluation was conducted using pre-test and post-test questionnaires to assess changes in participants’ knowledge levels. The results demonstrated a significant increase in knowledge following the intervention. Knowledge regarding the definition of menstruation increased from 45% to 82%, knowledge of menstrual hygiene products increased from 31% to 76%, understanding of the purpose of menstrual hygiene increased from 58% to 84%, and knowledge of proper menstrual hygiene practices increased from 31% to 92%. The high level of participant engagement and enthusiasm throughout the activities further reflected the effectiveness of the educational approach. In conclusion, health education delivered through presentations, discussions, and interactive question-and-answer sessions effectively enhanced adolescent girls’ knowledge and preparedness in maintaining menstrual hygiene during disaster situations.